PENGARUH PERSEPSI GAYA KEPEMIMPINAN MANAJER TERHADAP KEPUASAN KERJA KARYAWAN PADA PT PRIMAYUDHA MANDIRIJAYA BAGIAN QC - Cantika, Age Dwi; Soesilo, Tritjahjo Danny; Windrawanto, Yustinus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted with the aim of finding out whether there was an influence of managers' perceptions of leadership style on the job satisfaction of PT Primayudha Mandirijaya employees in the QC section. The population in this study were all employees of PT Primayudha Mandirijaya in the QC (Quality Control) section, totaling 58 employees. The data collection method used is using a questionnaire. The analysis technique used is Simple Linear Regression. Based on the results of the analysis, it shows that there is a significant influence between the Manager's Leadership Style on Employee Job Satisfaction, which can be proven at a value of sig = 0.000 < 0.05. The results of the research found that the coefficient of determination test between the Manager's Leadership Style and Employee Job Satisfaction was 61.1%, this figure shows that 61.1% of the Job Satisfaction that occurred was influenced by the Manager's Leadership Style and the remaining 38.9% was influenced by other factors. From the research results obtained, it is known that 12% of employees are satisfied with the directive leadership style, 18.9% of employees are satisfied with the supportive leadership style, 8.7% of employees are satisfied with the achievement leadership style, and 60.3% of employees are satisfied with the participative leadership style.